Ensuring leadership at the operational level of a health system in protracted crisis context: a cross-sectional qualitative study covering 8 health districts in Eastern Democratic Republic of Congo - Rosine N. Bigirinama; Samuel L. Makali; Mamothena C. Mothupi; Christian Z. Chiribagula; Patricia St Louis; Pacifique L. Mwene-Batu; Ghislain B. Bisimwa; Albert T. Mwembo; Denis G. Porignon (BMC, 2023)
Abstract Background This study examines how leadership is provided at the operational level of a health system in a protracted crisis context. Despite advances in medical science and technology, health systems in low- and middle-income countries struggle to deliver quality care to all their citizens. The role of leadership in fostering resilience and positive transformation of a health system is established. However, there is little literature on this issue in Democratic Republic of the Congo (DRC). This study describes leadership as experienced and perceived by health managers in crisis affected health districts in Eastern DRC. Methods A qualitative cross-sectional study was conducted in eight rural health districts (corresponding to health zones, in DRC's health system organization), in 2021. Data were collected through in-depth interviews and non-participatory observations. Participants were key health actors in each district. The study deductively explored six themes related to leadership, using an adapted version of the Leadership Framework conceptual approach to leadership from the United Kingdom National Health Service's Leadership Academy. From these themes, a secondary analysis extracted emerging subthemes. Results The study has revealed deficiencies regarding management and organization of the health zones, internal collaboration within their management teams as well as collaboration between these teams and the health zone's external partners. Communication and clinical and managerial capacities were identified as key factors to be strengthened in improving leadership within the districts. The findings have also highlighted the detrimental influence of vertical interventions from external partners and hierarchical supervisors in health zones on planning, human resource management and decision-making autonomy of district leaders, weakening their leadership. Conclusions Despite their decentralized basic operating structure, which has withstood decades of crisis and insufficient government investment in healthcare, the districts still struggle to assert their leadership and autonomy. The authors suggest greater support for personal and professional development of the health workforce, coupled with increased government investment, to further strengthen health system capacities in these settings.